Thermodynamic conditions of emulsion formation during autodispersion. - G. A. Grigoriev; E. V. Eskova; A. A. Andreyantseva; V. B. Ilinicheva (Тонкие химические технологии, 2009)
The thermodynamic conditions of emulsion formation are considered on the basis of perfect solution model. It is shown that the factor chosen arbitrarily in the article of Shchukin-Rebinder on the determination of critical surface tension, can be calculated on the basis of experimentally definable quantities. It is established that the thermodynamic conditions of the formation of emulsion from a two-phase initial state depend on the initial interphase tension and the structure of initial system. It is noted that the contribution of mixture enthropy to the general thermodynamical properties of the system becomes apparent at a high degree of the dispersiveness close to molecular one. To achieve the conditions of dispersion the introduction of the mechanical energy or the energy of the combined process proceeding at the interphase border in parallel with the dispersion process is necessary.